The Practice of Money Politics Among Generation Z in Medan City in the 2024 Legislative Elections - Jonny Marpaung; Heri Kusmanto; Tengku Irmayani (PT FORMOSA CENDEKIA GLOBAL, 2024)
This research is motivated by indications of money political practices that occur in every election, one of which is the 2024 legislative member election in Medan City. Indications of election fraud are proven by data released by the Coalition to Reject Fraudulent Elections in 2024 which stated that one of the violations in legislative elections was the practice of money politics. The practice of money politics that occurs in Indonesia, especially in the city of Medan, can threaten the political development process which will ultimately thwart democracy in Indonesia. One part that has a role in changing Indonesia's democratic system for the better is Generation Z. This background is the basis for the importance of research that is able to analyze the form and distribution pattern of money politics among Generation Z and the reasons why the practice of money politics occurs among Generation Z during elections. legislature in 2024 as well as prevention analysis practice money politics in every election, especially for generation Z. This research was conducted using descriptive qualitative methods with in-depth interview techniques and Focus Group Discussion. The results obtained are that the form of money politics is divided into two, namely direct transactions and indirect transactions. The distribution pattern of political money among generation Z begins with data collection by the success team, giving political money in halls, shops, eating places, or delivered home to the bus counter. The time for giving political money is the day before the election, the evening before the election, the morning before the election and the morning or afternoon after the election